Multifaceted effects of noisy galvanic vestibular stimulation on manual tracking behavior in Parkinson’s disease - Lee, Soojin; Kim, Diana J.; Svenkeson, Daniel; Parras, Gabriel; Oishi, Meeko Mitsuko K.; McKeown, Martin J. (Frontiers in Systems Neuroscience, 2015)
Parkinson’s disease (PD) is a neurodegenerative movement disorder that is characterized clinically by slowness of movement, rigidity, tremor, postural instability, and often cognitive impairments. Recent studies have demonstrated altered cortico-basal ganglia rhythms in PD, which raises the possibility of a role for non-invasive stimulation therapies such as noisy galvanic vestibular stimulation (GVS). We applied noisy GVS to 12 mild-moderately affected PD subjects (Hoehn & Yahr 1.5-2.5) off medication while they performed a sinusoidal visuomotor joystick tracking task, which alternated between 2 task conditions depending on whether the displayed cursor position underestimated the actual error by 30% (‘Better’) or overestimated by 200% (‘Worse’). Either sham or subthreshold, noisy GVS (0.1-10 Hz, 1/f-type power spectrum) was applied in pseudorandom order. We used exploratory (Linear Discriminant Analysis with bootstrapping) and confirmatory (robust multivariate linear regression) methods to determine if the presence of GVS significantly affected our ability to predict cursor position based on target variables. Variables related to displayed error were robustly seen to discriminate GVS in all subjects particularly in the Worse condition. If we considered higher frequency components of the cursor trajectory as “noise”, the signal-to-noise ratio of cursor trajectory was significantly increased during the GVS stimulation. The results suggest that noisy GVS influenced motor performance of the PD subjects, and we speculate that they were elicited through a combination of mechanisms: enhanced cingulate activity resulting in modulation of frontal midline theta rhythms, improved signal processing in neuromotor system via stochastic facilitation and/or enhanced “vigor” known to be deficient in PD subjects. Further work is required to determine if GVS has a selective effect on corrective submovements that could not be detected by the current analyses.